2003
DOI: 10.1038/sj.gene.6363963
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in lymphotoxin alpha and CD14 genes influence TNFα production induced by Gram-positive and Gram-negative bacteria

Abstract: Improved understanding of how host genetic variation affects resistance to microbial pathogens could lead to better treatment and/or prevention of infectious diseases. The lymphotoxin alpha (LTA)+250 and CD14À159 polymorphisms are associated with differences in susceptibility or outcome to several infections. We stimulated peripheral blood mononuclear cells (PBMC) from 22 healthy individuals with purified lipopolysaccharide (LPS), heat-killed Escherichia coli or Streptococcus pneumoniae. TNFaintracellular prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 24 publications
3
35
0
3
Order By: Relevance
“…One of these cases (case 16) carried the HLA-B*5701 allele and the Hsp70 region of the 57.1 AH but lacked the region from snRNP to MEGT1, expressing non-57.1 AH alleles at one SNP and two microsatellite loci in this region. The translated sequences of Hsp70.1 and Hsp70.2 were similar in abacavir-hypersensitive individuals (cases [15][16][17] and controls with recombinant 57.1 AHs (cases [19][20][21][22] and were therefore excluded as candidate susceptibility loci.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of these cases (case 16) carried the HLA-B*5701 allele and the Hsp70 region of the 57.1 AH but lacked the region from snRNP to MEGT1, expressing non-57.1 AH alleles at one SNP and two microsatellite loci in this region. The translated sequences of Hsp70.1 and Hsp70.2 were similar in abacavir-hypersensitive individuals (cases [15][16][17] and controls with recombinant 57.1 AHs (cases [19][20][21][22] and were therefore excluded as candidate susceptibility loci.…”
Section: Resultsmentioning
confidence: 99%
“…The centromeric boundary of the susceptibility region 3Ј of Hsp70.2 was demarcated by the presence of three non-57.1 AH alleles, one in each of the recombinant abacavir-hypersensitive individuals (cases [15][16][17]. In addition, the telomeric end of the hypersensitivity region is flanked by snRNP, as an abacavir-hypersensitive individual (case 16) carried non-57.1 AH alleles between snRNP and MEGT1 (identified by non-57.1 AH alleles at two microsatellites and one SNP loci).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in accordance with a study on patients with sepsis (2 ), which also reported no association between IL-6 genotype and systemic IL-6 concentrations in vivo (compare the findings in Table 1). Possibly other polymorphisms (35-37 ) may be overruling the putative effect of the IL-6 G(Ϫ174)C promoter polymorphism on the release of IL-6 into the circulation, such as the recently described polymorphisms in the Toll-like receptor 4 (38,39 ) or in the CD14 gene (40 ).…”
Section: Discussionmentioning
confidence: 99%
“…В ранее проведенных исследованиях in vivo и in vitro высказана гипотеза о влиянии полимор-физма гена СD14 на продукцию фактора некроза опухоли-альфа (TNFα), зависящую от характера микрофлоры; в частности, экспозиция данного цитокина должна быть различной в зависимости от преобладания грамположительной или грам-отрицательной микрофлоры [26].…”
Section: результаты и обсуждениеunclassified